2020
DOI: 10.1111/twec.13002
|View full text |Cite
|
Sign up to set email alerts
|

How trade and investment agreements affect bilateral foreign direct investment: Results from a structural gravity model

Abstract: foreign direct investment, preferential trade agreements, gravity model 1 | INTRODUCTION We estimate the potential impact of preferential trade agreements (PTAs)-and other bilateral policies that affect trade and investment-on the bilateral FDI stocks and flows between the countries signing these agreements. Our key results are based on a structural gravity model of FDI that is applied to bilateral FDI data from UNCTAD (2014), while controlling for the presence, heterogeneity and depth of preferential trade ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 67 publications
4
55
0
1
Order By: Relevance
“…Second, our paper is related to a large body of research assessing the effect of PTAs on trade and FDI. With few exceptions (Rose, 2004), this literature has found that PTAs have a large effect on trade flows between partner countries (Baier and Bergstrand, 2007;Büthe and Milner, 2008;Mansfield and Reinhardt, 2008;Baier et al, 2014;Büthe and Milner, 2014;Dür et al, 2014;Egger and Nigai, 2015;Osnago et al, 2017;Miroudot and Rigo, 2019;Laget et al, 2020;Kox and Rojas-Romagosa, 2020). Our results warn scholars that reverse causality is at play, leading to potentially overestimating the impact of preferential liberalization on trade activities.…”
Section: Introductionmentioning
confidence: 53%
“…Second, our paper is related to a large body of research assessing the effect of PTAs on trade and FDI. With few exceptions (Rose, 2004), this literature has found that PTAs have a large effect on trade flows between partner countries (Baier and Bergstrand, 2007;Büthe and Milner, 2008;Mansfield and Reinhardt, 2008;Baier et al, 2014;Büthe and Milner, 2014;Dür et al, 2014;Egger and Nigai, 2015;Osnago et al, 2017;Miroudot and Rigo, 2019;Laget et al, 2020;Kox and Rojas-Romagosa, 2020). Our results warn scholars that reverse causality is at play, leading to potentially overestimating the impact of preferential liberalization on trade activities.…”
Section: Introductionmentioning
confidence: 53%
“…Second, we contribute to the recent literature investigating the non-trade content of trade agreements (Borchert et al, 2020;Lecher, 2016) and its impact on trade (Carrère et al, 2017;Lopez Vicente et al, 2020;Osnago et al, 2020;Raess and Sari, 2018). The paper closest to ours is Kox and Rojas-Romagosa (2020). They investigate the impact of PTAs and bilateral investment treaties on FDI: we follow their approach in specifying our empirical exercise and extend the analysis to how NTIs in PTAs affect FDI.…”
Section: Introductionmentioning
confidence: 93%
“…Although the research question that we explore is novel to the literature, this paper places itself at the intersection of two main strands of the literature. First, we add to the studies investigating the economic effect of trade agreements (among many others, Baier and Bergstrand, 2007;Egger et al, 2011;Heid et al, forthcoming;Olivero and Yotov, 2012) and the effect on FDI in particular (Anderson et al, 2019;Bergstrand and Egger, 2007;2010;Chen, 2009;Kox and Rojas-Romagosa, 2020;Ramondo, and Rodríguez-Clare, 2013). Second, we contribute to the recent literature investigating the non-trade content of trade agreements (Borchert et al, 2020;Lecher, 2016) and its impact on trade (Carrère et al, 2017;Lopez Vicente et al, 2020;Osnago et al, 2020;Raess and Sari, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[3] These works include for example, Baccini et al (2017); Baltagi et al (2008); Büthe and Milner (2008); Cardamone and Scoppola (2012); Kox and Rojas-Romagosa (2020); MacDermott (2007); Medvedev (2012); Tekin-Koru and Waldkirch (2010) and Zahid (2020).…”
Section: Introductionmentioning
confidence: 99%